Effect of hemovigilance education on nursing students' knowledge: the application of a conceptual map - Behnammoghadam Mohammad; Fazelniya Zahra; Bayat Amir Hossein; Jahanfar Abdolhadi; Mirzaee Mohammad Saeed; Mirzaee Sobhan; Shahnavazi Allahyar; Mahmoudi Zeinab (Sciendo, 2022)
Given the importance of having knowledge on the hemovigilance process in nursing care, the present study was conducted to investigate the effect of the hemovigilance education on nursing students' knowledge using a conceptual map. The current research was a semi-experimental study.